Denser brain capillary network with preserved pericytes in Alzheimer's disease - Fernandez‐Klett, Francisco; Brandt, Lasse; Fernández‐Zapata, Camila; Abuelnor, Basim; Middeldorp, Jinte; Sluijs, Jacqueline A.; Curtis, Maurice; Faull, Richard; Harris, Laura W.; Bahn, Sabine; Hol, Elly M.; Priller, Josef (Brain pathology (Zurich, Switzerland), 2020)
Pericytes are vascular mural cells that surround capillaries of the central nervous system (CNS). They are crucial for brain development and contribute to CNS homeostasis by regulating blood–brain barrier function and cerebral blood flow. It has been suggested that pericytes are lost in Alzheimer's disease (AD), implicating this cell type in disease pathology. Here, we have employed state‐of‐the‐art stereological morphometry techniques as well as tissue clearing and two‐photon imaging to assess the distribution of pericytes in two independent cohorts of AD (n = 16 and 13) and non‐demented controls (n = 16 and 4). Stereological quantification revealed increased capillary density with a normal pericyte population in the frontal cortex of AD brains, a region with early amyloid β deposition. Two‐photon analysis of cleared frontal cortex tissue confirmed the preservation of pericytes in AD cases. These results suggest that pericyte demise is not a general hallmark of AD pathology.